PERSPECTIVE OF INNOVATION DRUG FORMULATION WITH DARUNAVIR ETHANOLAT - S. A. Zolotov; N. B. Diomina; G. F. Vasilenko; M. S. Demin (Разработка и регистрация лекарственных средств)
Article shows the results of development and technological issues of darunavir ethanolate in capsule form. Soluplus was used to increase the biopharmaceutical characteristics of current drug formulation. Results of dissolution profile studies shows that intensity and release rate of API from the capsules are proportional to concentration of solubilizer and close to comparator agent. Results of the studies have shown necessity to research the physical and chemical characteristics of darunavir ethanolate substances and it could be used in the development of an innovative dosage form.